Impact of social media on higher education: Academic performance, leadership and co-curricular activity engagement - Mohamed Sultan, Al Amin; Ismail, Erwan; Md Saad, Mohd Shamsuri; Husain, Afifuddin Husairi; Daud, Muhammad Zaid; M.Alswat, Haitham (Malque Publishing, 2025)
This study explores the perceptions of students at a Malaysian Technical University students toward social media use and its impact on cocurricular activities, leadership, and academic achievement. Using a quantitative cross-sectional survey, a questionnaire was administered to a population of 1,000 students, with 278 respondents determined using Krejcie and Morgan's sampling method. Data analysis included descriptive and inferential statistics. The study achieved a 99.6% response rate with 277 respondents, comprising 77% Malay, 12% Chinese, 8% Indian, and 3% from other races. Educational levels were predominantly bachelor's degrees (93%) and diplomas (7%). WhatsApp was the most frequently used social media application (23%), while other applications were the least used (1%). The highest average time spent on social media was for social purposes (µ = 3.30), followed by online gaming (µ = 2.78). A significant relationship was found between academic achievement and leadership (r = 0.369; p < 0.01). However, no significant relationship was identified between social media use and involvement in extracurricular activities, academic achievement, or leadership. Sleep deprivation is prevalent, with most students sleeping less than the recommended 7 hours per night. Despite this, many students still achieve high academic performance, indicating resilience and effective time management. Addressing sleep deprivation is crucial for maintaining cognitive function and overall health. The study concludes that while the students have considerable free time, social media usage does not significantly affect academic performance. Increased participation in extracurricular activities is recommended. Additionally, limiting social media use is advised for better health and well-being.